The Inheritance of Balo-Balo Art at the Cahaya Rembulan Musik Studio in Tegal City - Pratama, Rizki Giska; Hartono, Hartono; Triyanto, Triyanto (Catharsis, 2020)
The aim of this study is to analyze the inheritance of the balo-balo art performance and the inheritance of socio-cultural values carried out by the balo-balo art community. The method used is qualitative with ethnomusicology and anthropology approaches. The data collection techniques was conducted through observation, interviews, and documentation studies. The analysis process consists of data collection, data reduction, and data clarification. The results of the study on the inheritance of the balo-balo art include inheritance of the form of balo-balo art performance which was an effort to keep traditional arts. The inheritance was carried out at the Cahaya Rembulan Musik Studio by doing exercises, preparations, and balo-balo art performance. Balo-balo art poetry is in the form of wangsalan (poem) which contains of advice about God Almighty. The inheritance of socio-cultural values contain religious values which these values are contained in the lyrics and educational values that are inherited through training in balo-balo art which are expected to introduce traditional arts, especially balo-balo art to the Tegal City community.